2018
DOI: 10.4236/jbm.2018.63005
|View full text |Cite
|
Sign up to set email alerts
|

Role of Protein Kinase C<i>δ</i>-Mediated Spleen Tyrosine Kinase (Syk) Phosphorylation on Ser in the Amplification of Oral Mucosal Inflammatory Responses to <i>Porphyromonas gingivalis</i>

Abstract: The signaling events underlying oral mucosal inflammatory responses to P. gingivalis and its key endotoxin, lipopolysaccharide (LPS), relay primarily on the LPS engagement of Toll-like receptor-4 (TLR4), and the activation of IκB-kinase complex (IKK) and mitogen-activated protein kinases (MAPKs that exert their control over transcription factors implicated in the regulation of iNOS and COX-2 proinflammatory genes expression). Since spleen tyrosine kinase (Syk) has emerged recently as a major amplifier in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Based on the ligand recognition and binding, TLR4 is now well-documented as a receptor that mediates inflammatory responses to bacterial LPS, including that of P. gingivalis [25] [26] [27]. Indeed, studies show that the exposure of salivary gland acinar cells to P. gingivalis LPS results in the TLR4 activation through autophosphorylation ( Figure 1) on several critical Tyr residues that are essential for the initiation of downstream signaling events [42].…”
Section: Structure and Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the ligand recognition and binding, TLR4 is now well-documented as a receptor that mediates inflammatory responses to bacterial LPS, including that of P. gingivalis [25] [26] [27]. Indeed, studies show that the exposure of salivary gland acinar cells to P. gingivalis LPS results in the TLR4 activation through autophosphorylation ( Figure 1) on several critical Tyr residues that are essential for the initiation of downstream signaling events [42].…”
Section: Structure and Activationmentioning
confidence: 99%
“…The first step in Syk activation is its binding through SH2 domains to the intracellular Toll-IL-1 receptor (TIR) domain of TLR4 or signaling proteins containing phosphorylated immunoreceptor tyrosine-based activation motifs (ITAMs) in their cytoplasmic regions[103]. This results in conformational changes in Syk and its activation through phosphorylation on several tyrosine residues, which leads to the activation of the PLC, PI3K, MAPK and ERK signaling cascades, and amplification in the induction of inflammatory response[103] [104].Therefore, to gain further leads into the pathways utilized by P. gingivalis en-dotoxin, LPS, in triggering up-regulation in oral mucosal inflammatory responses, we investigated the nature of factors involved in the recruitment and interaction of Syk with TLR4 in salivary gland acinar cells in response to stimulation by P. gingivalis LPS[42]. By following the acinar cell TLR4 activation and its interaction with Syk, we found that stimulation with the LPS led to a rapid,time-dependent induction in the phosphorylation of TLR4 and Syk on Tyr, and that the association between Syk and TLR4 induced by the LPS required phosphorylation of both proteins on Tyr.…”
mentioning
confidence: 99%